2014
DOI: 10.2341/12-269-l
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Resin Bond Strength to Yttria-stabilized Tetragonal Zirconia and Framework Marginal Fit: Comparison of Different Surface Conditionings

Abstract: The low-fusing glass application followed by hydrofluoric acid etching and silanization seems to be a promising method for improving the resin bond strength to yttria-stabilized tetragonal zirconia, but the adhesion to this substrate is still a challenge. SUMMARYThe purpose of this study was to evaluate the effect of different surface treatments of yttriastabilized tetragonal zirconia (Y-TZP) on bond strength durability and marginal discrepancies. For adhesion testing, 144 specimens of VITA In-Ceram YZ ceramic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
4
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 56 publications
6
66
4
7
Order By: Relevance
“…Surface treatments have been studied on zirconia to improve bond compatibility between the two ceramics and appear to be important to improving bond strength (13,(15)(16)(17)(18)(19). The present work found that porcelain glaze application on the zirconia core before veneering porcelain cylinder build-up promoted zirconia-porcelain bond improvements, while the untreated group showed the lower bond strength result.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Surface treatments have been studied on zirconia to improve bond compatibility between the two ceramics and appear to be important to improving bond strength (13,(15)(16)(17)(18)(19). The present work found that porcelain glaze application on the zirconia core before veneering porcelain cylinder build-up promoted zirconia-porcelain bond improvements, while the untreated group showed the lower bond strength result.…”
Section: Discussionmentioning
confidence: 49%
“…In addition, the thickness and chemical composition of the film can also be controlled. Another positive factor of the nano-coating is its nanometer thickness (13,19) . A previous study showed that nanofilm could be a favorable alternative to the deposition of silica on the Y-TZP (13), promoting high bonding strength among ceramics.…”
Section: Discussionmentioning
confidence: 99%
“…A strong resin bond can be established by the application of a silane coupling agent followed by a resin-based adhesive system. Other non-air-abrasion approaches to obtain chemical bond to zirconia using silane plus resin adhesives have been reported, including low fusion glass coating [38], silica-based chemical coating [39], and vapor phase deposition [40]. However, the stability of the interfacial bond among zirconia, coating, and cement and the influence of the coating on the fitting of the restoration are still questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies has shown promising results on bond strengths of Y-TZP/resin cement after glazed ceramic surface is subjected to air-particle abrasion with aluminum oxide and silanization [1] or etching with hydrofluoric acid [75], but a stable bond promoted by these methods is questionable and needs more studies.…”
Section: Alternative Treatmentsmentioning
confidence: 99%